Desfase en dirección única - Tomsich, Francisco (Ars et humanitas, 2017)
This article deals with some problems that we face when comparing recent art histories from Eastern Europe and South America. The focal case is the origins of video art in Uruguay and Slovenia. The first section poses the question of the origins of video art in general as one of the many issues that make it very difficult to produce narratives on the medium%s history, an aspect which has great political and aesthetic consequences. We postulate a typological model of classification of pioneering works of video art in order to acquire some useful tools to compare the very dissimilar panoramas of Uruguay and Slovenia regarding video art historiography and archiving. The gap between the pioneering production of video art (understood as using magnetic tape) in Uruguay and Slovenia calls into question the common practice of referring to both countries as on similar margins of the hegemonic artistic centres. We analyse those works considered foundational of video art production in Slovenia (Belo mleko belih prsi, Srečo and Nuša Dragan, 1969) and Uruguay (I%m on the way, Grupo Teatro Danza de Montevideo, 1982), in order to outline the difficulty of establishing operative comparisons between the political and social contexts in which these practices emerged, a difficulty that nevertheless acts as a stimulus to produce new approaches to contemporary cultural and artistic phenomena, both in Uruguay and Slovenia.
Keywords: alternativna kultura; diktatura; konceptualizem; Slovenija; Urugvaj; videoumetnost